Glenohumeral internal rotation deficit: insights into pathologic, clinical, diagnostic, and therapeutic characteristics - Mohamad Y. Fares; Jad Lawand; Mohammad Daher; Joyce D. Suarez; Theodore Kayepkian; Jonathan Koa; Eddie Geagea; Joseph A. Abboud (Clinics in Shoulder and Elbow)
Overhead throwing athletes undergo significant biomechanical adaptations due to repetitive overhead movements, primarily affecting the glenohumeral joint. These adaptations can lead to glenohumeral internal rotation deficit (GIRD), which is characterized by posterior capsule stiffness that results in glenohumeral joint translation and a shift in the center of gravity. The severity of GIRD is dependent upon the presence of asymmetry between gained external and lost internal rotation, which is defined clinically as an asymmetry exceeding 20º; this reduces the total range of motion compared to the unaffected limb or baseline measurements. Diagnosis is challenging, as it can be mistaken for chronic scapular adaptations. To mitigate misdiagnosis, a high clinical suspicion is crucial in overhead athletes, especially those who began performing forceful overhead movements before closure of growth plates. Periodic physical examinations should establish baseline values for glenohumeral rotation and track changes in glenohumeral motion to aid in diagnosis. Symptoms of GIRD include shoulder pain, stiffness, and decreased force exertion. Magnetic resonance imaging is the preferred imaging method for evaluating GIRD and assessing concomitant soft tissue pathologies. Untreated GIRD can lead to rotator cuff strength imbalances. Treatment mainly involves conservative measures, such as physical therapy, to improve internal rotation and alleviate posterior tightness. Surgical interventions are considered when symptoms persist despite conservative treatment with physical therapy or in the presence of concomitant pathologies.